2006
DOI: 10.1002/pd.1504
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of fetal DNA levels in maternal plasma with Doppler status in pathological pregnancies

Abstract: Increased fetal DNA levels in maternal plasma may be a sign of placental or fetal pathology even in the presence of normal uterine Doppler velocimetry, allowing a more precise diagnostic evaluation. The finding that elevated fetal DNA in IUGR pregnancies correlates with abnormal umbilical Doppler velocimetry suggests that fetal DNA release is associated more with fetal chronic hypoxia than with fetal size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 27 publications
1
21
0
5
Order By: Relevance
“…Previous studies reported that plasma cfDNA levels are increased in pregnancies with clinically established PE [13,14,15,16], which has been attributed to placental ischemia, with release into the maternal circulation of necrotic or apoptotic syncytiotrophoblast fragments that contain fetal cfDNA [15,35]. Some contradictory evidence suggests that in cases of early-onset PE the increase in cfDNA precedes the clinical onset of the disease and may be apparent from the first trimester of pregnancy [35,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that plasma cfDNA levels are increased in pregnancies with clinically established PE [13,14,15,16], which has been attributed to placental ischemia, with release into the maternal circulation of necrotic or apoptotic syncytiotrophoblast fragments that contain fetal cfDNA [15,35]. Some contradictory evidence suggests that in cases of early-onset PE the increase in cfDNA precedes the clinical onset of the disease and may be apparent from the first trimester of pregnancy [35,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in pregnancies with male fetuses in which maternal plasma cfDNA level was estimated by amplification loci on the Y-chromosome reported that there is a 2- to 5-fold increase in cfDNA in preeclampsia (PE), which is associated with impaired placentation reflected in low first-trimester serum PAPP-A [12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, amniotic fluid concentration of S100B was found to sensitively and specifically predict spontaneous intrauterine fetal death (Florio et al 2004). Although an early study conducted by Sekisawa et al found no significant difference in maternal plasma levels of cffDNA in nine women with IUGR compared with 20 gestation age-matched controls (Sekizawa et al 2003), more recent studies using larger cohorts found significant increases in women with IUGR (Smid et al 2006, Al Nakib et al 2009, Alberry et al 2009. Similarly, circulating mitochondrial DNA was also found to be increased in patients with IUGR (Colleoni et al 2010).…”
Section: Intrauterine Growth Restrictionmentioning
confidence: 99%
“…However, due to the rare occurrence of these cells the much more likely source of cff DNA in maternal plasma is the placenta (Bianchi, 2004;Alberry et al, 2007). The kinetics of cff DNA accumulation in maternal plasma also suggest that the placenta is the likely source as cff DNA levels increase with gestational age (Birch et al, 2005;Galbiati et al, 2005;Smid et al, 2006). It is known from in vitro studies that hypoxia induces both apoptosis and necrosis in villous explants of the placenta, with an accompanying release of cellfree DNA.…”
Section: Origins Of Cell-free Plasma Dna and Identifying Biomarker Dmentioning
confidence: 99%